Há sinergia entre o sistema lean manufacturing e a gestão ambiental? mapeando o estado da arte - Ferreira, Marco Antonio; Santos, Renê de Oliveira Joaquim dos; Stefanelli, Nelson Oliveira; Jabbour, Charbel José Chiappetta [UNESP] (LATEC, 2015)
In recent decades, two research themes have been prominent in the academic and organizational setting: lean manufacturing and green management. Since 1996, when Florida (1996) wrote an article focusing on the synergy between these two areas, the debate if “Lean is Green?” enters in the academic field. It is in this context that this research presents the results of a systematic literature on the topic, focusing on the characteristics, positive and negative impacts, lean paradigms, green paradigms and design of supply chains. To perform this procedure it were followed the methodological footsteps of Lage Junior and Godinho Filho (2010). The research occurred in the database Scopus and it was conducted from June, 2012 to July, 2012.The key word used was “green lean” and as search filter it were included only articles and conference Papers. Their main result is a deep analysis of the accumulated knowledge on the subject, where it is revealed that the majority of studies point to the synergy between some components of the lean manufacturing system in relation to environmental management. The research gap found is related to articles that address the entropy of the union of lean and green systems.

Nas últimas décadas, dois temas de pesquisa têm se destacado no cenário acadêmico e organizacional: lean manufacturing e gestão ambiental. Desde 1996, quando Florida (1996) publicou um artigo enfocando a sinergia entre as duas áreas, o debate sobre o tema “Lean é Green?” ganhou espaço no âmbito acadêmico. É neste contexto que se pretende identificar: qual o estado da arte da literatura Lean é Green? Os resultados encontrados estão divididos em: características, impactos positivos e negativos, paradigmas lean, paradigmas green e design da cadeia. Para a realização de tal procedimento, foram seguidos os passos metodológicos de Lage Junior et Godinho Filho (2010) tendo sido pesquisados os trabalhos contidos no portal Scopus. A pesquisa foi realizada entre 01-06-2012 e 15-07-2012, e a palavra chave utilizada foi green lean; como filtro de pesquisa foram considerados apenas artigos e papers de conferência. O seu principal resultado é uma análise aprofundada do conhecimento acumulado sobre o tema, em que foi identificado que a maioria dos estudos realizados apontam para a sinergia entre alguns componentes do sistema lean manufacturing em relação à gestão ambiental. Já a lacuna de pesquisa encontrada refere-se a artigos que enfocam as entropias da união dos sistemas lean e green.
Is there any synergy between lean manufacturing and green management? mapping the state-of-the-art
Keywords: Green management; Lean production; Systematization; Lean manufacturing; Gestão ambiental; Sistematização